Reasons associated with preservice teachers' intention to use immersive virtual reality in education. (3rd August 2020) - Bower, Matt; DeWitt, Dorothy; Lai, Jennifer W. M.
Abstract : Abstract: The recent interest in the use of Immersive Virtual Reality (IVR) in education seems to correspond with the increased affordability, accessibility and functionality of IVR hardware and software. IVR has the potential to enhance immersion, improve spatial capabilities, promote empathy, increase motivation and possibly improve learning outcomes. However, the extent to which teachers capitalise on these potentials in the future depends their perceptions of IVR and their behavioural intentions to use it. Accordingly, this study aimed to identify relevant factors and influences relating to preservice teachers' behavioural intention to use IVR, using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. Confirmatory factor analysis revealed that UTAUT2 provided a suitable model to describe preservice teachers' perceptions of IVR on all dimensions (performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit and behavioural intention), with hedonic motivation receiving the highest scores and habit scoring the lowest. Interview responses revealed the reasons for the substantial variation in preservice teacher perceptions, which depended on a range of external‐ ("first‐order"), internal‐ ("second‐order") and design ("third‐order")‐related issues. Implications for schools, educational leaders and teacher education are discussed. Practitioner Notes What is already known about this topic Immersive virtual reality (IVR) can offer numerous benefits for educators, though there are several issues that teachers need to overcome to use IVR effectively. A range of external, internal or design related factors can impact on teacher propensity to use technology in the classroom. The Unified Theory of Acceptance and Use of Technology model (UTAUT2) has been applied to analysing behavioural intentions to use various technologies in education, but not Immersive Virtual Reality. What this paper adds Preservice teachers rated hedonic motivation (enjoyment) highest and habit lowest, which was different to other technology acceptance studies. A range of external barriers (access, logistics and support), internal barriers (attitudes, experience) and design issues (technical skills, ideas for pedagogically meaningful tasks) constrained intentions to use IVR. Validation of the UTAUT2 model applied to a novel technology (IVR) and cohort (preservice teachers), with the rare inclusion of qualitative findings to add explanatory power. Implications for practice and/or policy There is opportunity for teacher education programmes and school systems to leverage the enjoyment factor as a means of realising other benefits of IVR (visualisation, empathy and retention). Teachers need to be provided with access to devices, professional learning, technical guidance, time and a supportive school and policy environment to become confident and capable users of IVR. In order for teachers (and students) to become effective designers with IVR they not only require technical assistance but also support to understand how IVR can be used in pedagogically meaningful ways.